On food security stocks, peace clauses, and permanent solutions after Bali - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2014)
This paper focuses on the Ministerial Decision on “Public Stockholding for Food Security Purposes, WT/MIN(13)/W/10,”4 and analyzes a series of legal and economic aspects involved, trying to place the discussion in the context of the significantly different economic scenario since the Doha Development Round started. This changed context includes the new scenario for food prices, the important advances of developing countries in incomes, the parallel im-provements in hunger indicators along with the continuous advance of the “triple burden” of malnutrition, significant increases in agricultural production and trade, and in policy support to the sector in developing countries, along with more diversified diets and new food retail channels, even among the poor and in rural regions.